Antimicrobial property of photocatalytic nanoparticles-coated personal protective equipment (PPE) on bacteria and fungi - Subash Nambiar Sree Pathi; Noraziah Mohamad Zin; Nurul Amira Abd Rahim; Nur Faizah Abu Bakar; Wong, Kon Ken (Penerbit Universiti Kebangsaan Malaysia, 2023)
Photocatalytic nanoparticles are new applications that can be used as coatings on surfaces through a photocatalytic process that reacts in the presence of chemical catalysts and light. The resulting reactive oxygen species (ROS) would damage pathogenic components and result in antimicrobial effects. This study was conducted to evaluate the antimicrobial properties of photocatalytic nanoparticles on personal protective equipment (PPE), namely surgical gowns and masks. Antimicrobial testing of photocatalytic nanoparticles against PPE inoculated with pathogens was carried out. The growth log reduction of isolates tested on the photocatalytic nanoparticles-coated PPE showed 100% with growth reduction exceeding 4 log against Escherichia coli ATCC 25922 as well as Staphylococcus aureus ATCC 25923 but less than 50% reduction against Candida albicans ATCC 10231. For 20 h incubation periods, both bacteria showed growth reduction of at least 4 log with 99.99% of reduction. The 5 and 20 times washing effects showed an overall reduction of 99.99%-100% against both bacteria but less than 99.99% against C. albicans. Photocatalytic nanocoating produces an antimicrobial effect that helps to kill the tested pathogens and reduce the attachment of bacteria but not fungi, on the surface of PPE. This nanoparticle is capable of continuous self-disinfection to reduce the number of pathogens. The number of washing cycle also does not affect its function to reduce the growth of pathogens.